Corporate Performance and Governance in Malaysia - Leruth, Luc (IMF Working Papers; Working Paper, 2002)
This paper measures corporate sector performance (efficiency) and empirically examines the role of corporate governance. A stochastic frontier with inefficiency effects is fitted to a panel dataset of 31 of the largest nonfinancial companies listed on the Kuala Lumpur Stock Exchange for the period 1995 to 1999. Focusing specifically on the impact of the system of corporate governance and the level of control on firm-level performance, results show an underlying vulnerability in these firms, exacerbated by their reliance on bank-based borrowing and a highly concentrated shareholding structure with complex cross holdings. Furthermore, debt does not appear to have the control features present in outsider systems of corporate governance.